The Influence of Technical Skills and Soft Skills Development on Enhancing Employee Competence at PD Alam Aneka Aroma Sukabumi - Nurkhaila, Siti Nazwa; Zafar, Tetty Sufianti; Mulia Z, Faizal (Universitas Muhammadiyah Pontianak, 2025)
This study examines the effect of technical skills and soft skills development on employee competence at PD Alam Aneka Aroma Sukabumi. A quantitative associative method was applied to 35 employees. Data were analyzed using classical assumption tests, multiple linear regression, and hypothesis testing. The results showed soft skills development significantly influenced employee competence, while technical skills had no significant impact. These findings highlight the crucial role of soft skills development in human resource improvement strategies